Kajian Pengembangan Budidaya Ikan Kerapu dan Rumput Laut di Perairan Timur Pulau Serangan - Sari, Septi Novita; Nyoman Nurweda, I Dewa; Faiqoh, Elok; Giri Putra, I Nyoman (Journal of Marine Research and Technology; Vol 2 No 2 (2019): AGUSTUS 2019, 2019)
Aquaculture in Indonesia is able to contribute more than 80% of state money in 2012 contributed USD 5.9 billion. Aquaculture of various commodities has fulfilled the needs of both domestic and international markets. Various areas in Bali have contributed in contributing fisheries production one example is the island of Serangan. Serangan northern island area, has been used as a center for fishery cultivation of floating net floating net (KJA) of Fish and Seaweed in small scale. The main commodities of marine aquaculture in Serangan that are now developed are various types of Ornamental Fish, Sea Horse, Fish Beronang, Grouper Fish and Lobster. In addition to marine aquaculture, seaweed cultivation has grown the region is one type of Euchema cottoni. Current conditions, in the northern Attic has been dense with the existing tourism around the KJA. So that causes the condition of sea traffic in the northern waters is quite crowded so it can affect the cultivation activity. It is known that the income of the community. The biggest and biggest attack is the income from the cultivation fishery. In order to maintain existing cultivation and to meet market needs. So the author aims to examine the study of the suitability of location for the cultivation, especially seaweed and grouper, because the market demand of these two commodities is very high. The expected location of the writer is the eastern area of Serangan. In analyzing the data used scoring system method. The results of this study found that from the three locations of observation, station 1 is quite appropriate for the location of seaweed and grouper cultivation.